The results of experimental research of a rotor seed-metering unit for sowing non-free-flowing seeds - Shinar Ospanova; Mubarak Aduov; Sultan Kapov; Alexander Orlyansky; Kadirbek Volodya (Journal of Agricultural Engineering, 2024)
The production and cultivation of new high-quality seed varieties are linked to the sowing of various crops with diverse physical and mechanical seed properties. Efficient seed-metering unit operation is critical during the technological process of fodder crop cultivation, predominantly when sowing non-free-flowing seeds. The quality of seed sowing and crop yield significantly rely on the design precision of seed-metering devices, technical maintenance and appropriate calibration. A rotary seed metering device was incorporated to ensure that non-friable seeds are uniformly sown, thus maintaining consistent seed supply and consumption at all stages of circulation. The study of the proposed device's productivity dependence on its operating parameters is justified because these variables affect crucial indicators such as the capacity to achieve and sustain the desired seeding rate over the entire operational duration. The study presents findings from an experimental investigation on sowing non-free-flowing (non-flowing) and finely dispersed seeds using a rotor seed-metering unit. The tests aimed to ascertain the precision and evenness of sowing such crops. It was observed that the speed of rotation of the seed-metering unit's vane disk is a key factor in the uniformity and supply of sown seeds. The limits of variation in rotor rotation speed and rotor seed-metering unit productivity per second were established to guarantee the desired seeding rate for various crops, including alfalfa, Agropyron, and Bromus inermis.